Contralateral lateral rectus muscle recession in a patient with unilateral exotropic Duane retraction syndrome type II: A case report. (2nd January 2021) - Mao, Keli; Yan, Xiaohe; Ding, Kun; Chen, Lifei; Lin, Xiaoming
ABSTRACT: A fixation preference for the affected eye is uncommon in patients with unilateral Duane retraction syndrome (DRS), and surgery on the fellow eye is rarely advocated. We are presenting a case report of a 9-year-old boy with unilateral DRS type II in the left eye who received lateral rectus muscle recession in his right amblyopic eye. The patient was orthophoric and his face turn was gone 6 months postoperatively. Surgery on the fellow amblyopic eye is a good choice for unilateral DRS where the affected eye dominants the fixation, and the satisfactory outcome suggests that alignment in the primary position can correct the face turn effectively despite the muscle duction deficit in the affected eye and further extend the binocular single visual field.